Management of thyroid cancer during pregnancy - Reyna-Villasmil, Eduardo (2021)
Pregnancy is a favorable condition for the formation and growth of thyroid cancer, since the iodine balance can be negative in addition to increasing the production of hormones with thyroid stimulating activity. Most of the cancers found during pregnancy are differentiated thyroid cancers with an excellent prognosis. Those cases diagnosed during the first trimester can be removed by surgery. Thyroidectomy can be safely performed in the second trimester of pregnancy or delayed to the postpartum period, depending on gestational age. The patient should receive levothyroxine at a dose sufficient to keep serum thyroid-stimulating hormone levels low. Serum thyroglobulin is a valuable noninvasive method for evaluating the effects of this treatment. The purpose of this review is to establish the management of thyroid cancer during pregnancy.